Naturally-primed life strategy plasticity of dimorphic Aethionema arabicum facilitates optimal habitat colonization - Bhattacharya, Samik; Sperber, Katja; Özüdoğru, Barış; Leubner-Metzger, Gerhard; Mummenhoff, Klaus (Scientific reports, 2019)
Plasticity in plant dispersal traits can maximise the ability of a plant species to survive in stressful environments during colonization. Aethionema arabicum (Brassicaceae) is a dimorphic annual species that is hypothesized to survive stressful conditions during colonization due to adaptive plasticity in life-phase (vegetative vs sexual) and fruit morph (dehiscent [DEH] vs indehiscent fruits [IND]). We tested for adaptive plasticity in life-phase and fruit morphs along laboratory environmental stress gradients found in the natural habitats of Ae. arabicum. We considered optimal environmental conditions (750-2000 m above sea level) to be those that resulted in the following fitness parameters: higher biomass and a higher total number of fruits compared to stressful habitats. We found evidence of plasticity in life-phase and fruit-morph along a stressful environmental gradient. High hydrothermal stress proportionally increased the number of dehiscent morphs and non-dormant seeds germinating in autumn. This offsets natural phenology towards dry and cold winter (less hydrothermal stress), yielding fewer fruits that dehisce in the next generation. We conclude that the plastic responses of Ae. arabicum to natural stress gradients constitute a strategy of long-term adaptive benefits and favouring potential pathways of colonisation of the optimal habitat.
Keywords: fyziologický stres; Stress, Physiological; ekosystém; ovoce; Ecosystem; Adaptation, Physiological; Brassicaceae; Germination; fyziologická adaptace; Seeds; Fruit; klíčení; semena rostlinná